Analyzing liquefaction potential of municipal solid waste fines with fibers: a study on energy method and correlation models - Rawat P.; Mohanty S. (My University, 2025)
This study includes the reusability of the municipal solid waste (MSW) fines and fiber-reinforced MSW fines, where fibers are also the part of the waste. The investigation focuses on the liquefaction susceptibility of the considered waste using energy method. A total of 57 cyclic triaxial tests were conducted on MSW fines considering 5 parameters, i.e., relative compaction (Rc), frequency (f), effective confining pressure (σ′c), shear strain (γ), and fiber content (FC). The obtained data were further used for simplified models through the developed correlations. The cumulative dissipated energy at liquefaction of MSW fines was found to be significantly higher than that of sands and similar types of waste. The fibers under consideration show no improvement in the liquefaction resistance of the MSW fines. The developed correlations between the energy and the excess pore water pressure ratio, and energy and shear modulus ratio aid in predicting the behavior of waste under dynamic loading conditions. Regression models achieve R2 > 0.9 for excess PWP and energy ratios, R2 ≈ 0.99 for shear modulus and energy ratio, and R2 > 0.7 for dissipated energy prediction, with a new FC/γ ratio introduced for reinforced MSW fines. The relationship developed by regression models between different parameters and dissipated energy can be applied to other types of waste with similar nature. © The Author(s), under exclusive licence to Springer Nature Japan KK, part of Springer Nature 2024.